21st Century Windows: Electrochromic Windows and Other Glazing Technologies - Stephen E. Selkowitz (Fenestration Magazine, 2000)
One of our challenges for the 21st century will be to try to reduce adverse societal impacts on our planet. Buildings account for one of the nations largest energy costs and are the biggest source of greenhouse gas emissions. Within the building sector, windows were historically viewed as one of the weak links in buildings. The early response to this perspective was legislation to restrict window usage. The big conceptual leap in the last 25 years has been the recognition that better window technology and better building design can not only reduce these negative impacts, but can convert them into tangible human and economic benefits. The window industry has risen to the challenge of producing the cost-effective products that help translate researchers predictions into market reality. A look at trends in glazing and new findings from an electrochromic window study by the Lawrence Berkeley National Laboratory (LBNL) provides some additional clues on where fenestration technology will take us in the 21st Century.Two notable achievements have marked progress for the window industry in the last 25 years: Low-E coatings and spectrally selective cool glazings.